Complete female-transmitted mitochondrial genomes of two freshwater mussels from the Lake Biwa system in Japan: Nodularia douglasiae and N. nipponensis - Kohji Mabuchi; Kazuya Nishida; Nobuyoshi Nakajima (Mitochondrial DNA. Part B. Resources, 2021)
We determined the complete mitochondrial sequences of female-transmitted (F) mitogenomes of two unionid specimens from the Lake Biwa system, Japan. Their gene contents and orders agreed with those of the typical F mitogenome of freshwater mussels. Molecular phylogenetic analysis using 20 previously identified partial COI and seven (five previously identified and two newly determined) whole mitogenome sequences revealed that one of the two mitogenomes was that of Nodularia douglasiae, while the other was N. nipponensis.